Research of the dynamics of a physical pendulum forced with an electromagnetic field - Ogińska, Ewelina; Grzelczyk, Dariusz; Awrejcewicz, Jan (Wydawnictwo Politechniki Łódzkiej, 2021)
In this paper, both experimental and numerical results of the dynamics of a pendulum with a neodymium magnet and an aerostatic bearing are presented. The experimental stand includes the pendulum with the neodymium magnet at the end of the rod, whereas four electric coils are placed underneath. The pivot of the pendulum is supported on the aerostatic bearing. As a result, dry friction resistance in the pivot joint can be negligible and it has only a viscous character. The electric current with a given frequency and duty cycle and of a square waveform flows through the coils. Interaction between the neodymium magnet and the electric coils leads to the forced angular motion of the pendulum with the neodymium magnet. Both mathematical and physical models with experimentally confirmed system parameters are derived. The results of the simulation and experiment showed rich dynamics of the system, including various types of regular motion (multi-periodicity) and chaos.
Keywords: nonlinear dynamics; electromagnetic field; physical pendulum; aerostatic bearing; dynamika nieliniowa; pole elektromagnetyczne; wahadło fizyczne; łożysko aerostatyczne